Intragastric administration of short chain fatty acids greatly reduces voluntary ethanol intake in rats - María Elena Quintanilla; Daniela Santapau; Eugenio Diaz; Ignacio Valenzuela Martinez; Nicolas Medina; Glauben Landskron; Antonia Dominguez; Paola Morales; David Ramírez; Marcela Hermoso; Belén Olivares; Pablo Berríos-Cárcamo; et al. (Scientific Reports)
Abstract Alcohol use disorder (AUD) represents a public health crisis with few FDA-approved medications for its treatment. Growing evidence supports the key role of the bidirectional communication between the gut microbiota and the central nervous system (CNS) during the initiation and progression of alcohol use disorder. Among the different protective molecules that could mediate this communication, short chain fatty acids (SCFAs) have emerged as attractive candidates, since these gut microbiota-derived molecules have multi-target effects that could normalize several of the functional and structural parameters altered by chronic alcohol abuse. The present study, conducted in male alcohol-preferring UChB rats, shows that the initiation of voluntary ethanol intake was inhibited in 85% by the intragastric administration of a combination of SCFAs (acetate, propionate and butyrate) given before ethanol exposure, while SCFAs administration after two months of ethanol intake induced a 90% reduction in its consumption. These SCFAs therapeutic effects were associated with (1) a significant reduction of ethanol-induced intestinal inflammation and damage; (2) reduction of plasma lipopolysaccharide levels and hepatic inflammation; (3) reduction of ethanol-induced astrocyte and microglia activation; and (4) attenuation of the ethanol-induced gene expression changes within the nucleus accumbens. Finally, we determined that among the different SCFAs evaluated, butyrate was the most potent, reducing chronic ethanol intake in a dose–response manner. These findings support a key role of SCFAs, and especially butyrate, in regulating AUD, providing a simple, inexpensive, and safe approach as a preventive and intervention-based strategy to address this devastating disease.